2016
DOI: 10.2147/tcrm.s97342
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal ketorolac for the treatment of chronic cystoid macular edema after cataract surgery

Abstract: PurposeTo report two cases of chronic postoperative cystoid macular edema, resistant to topical therapy, treated with consecutive intravitreal injections of ketorolac tromethamine.MethodsFour daily intravitreal injections of 500 μg/0.05 mL of ketorolac were given to each patient. Complete clinical examination and OCT were performed before every injection, 1, 2, 3 weeks, and 1, 3, and 6 months after the last injection. Fluorescein angiography was performed at baseline examination, 1, 3, and 6 months after the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“… 5 Options for prevention of ME after cataract surgery in patients with NPDR include preoperative treatment with steroids, intravitreal injections of anti-VEGFs, laser treatment, and topical NSAIDs. 17 It seems more prudent to prevent PCME rather than treat it, since treatment usually involves more invasive methods like intravitreal NSAID, 25 subtenon triamcinolone, 26 or intravitreal dexamethasone implant injections. 6 Boscia et al suggested that all diabetic patients undergoing cataract surgery should be treated with topical NSAIDs to prevent PCME.…”
Section: Need For Prophylaxismentioning
confidence: 99%
“… 5 Options for prevention of ME after cataract surgery in patients with NPDR include preoperative treatment with steroids, intravitreal injections of anti-VEGFs, laser treatment, and topical NSAIDs. 17 It seems more prudent to prevent PCME rather than treat it, since treatment usually involves more invasive methods like intravitreal NSAID, 25 subtenon triamcinolone, 26 or intravitreal dexamethasone implant injections. 6 Boscia et al suggested that all diabetic patients undergoing cataract surgery should be treated with topical NSAIDs to prevent PCME.…”
Section: Need For Prophylaxismentioning
confidence: 99%
“…Options for prevention of macular edema after cataract surgery in patients with non-proliferative diabetic retinopathy include preoperative treatment with steroids, intravitreal injections of anti-VEGFs, laser treatment, and topical NSAIDs. It seems more prudent to prevent PCME rather than treat it, since treatment usually involves more invasive methods like intravitreal NSAID, 111 subtenon triamcinolone, 112 or intravitreal dexamethasone implant injections. Boscia et al suggested that all diabetic patients undergoing cataract surgery should be treated with topical NSAIDs to prevent PCME.…”
Section: Differential Diagnosis Of Cmementioning
confidence: 99%